2022
DOI: 10.1097/nna.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Equipping Nurses to Lead Evidence-Based Practice

Abstract: The aim of this study was to describe the evidence-based practice (EBP) attributes among California nurse leaders who are members of a professional nursing organization. BACKGROUND: Nurse leaders are pivotal for successful EBP implementation. The Association of California Nurse Leaders' (ACNL) mission to equip nurses to lead self, others, and systems propelled them to conduct a study of members' EBP beliefs, knowledge, competencies, and implementation. METHODS: Evidence-based practice attributes of California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Magnet designation moved organizations toward nursing excellence by supporting organizational EBP implementation as a scholarly activity, as well as a core requirement for designation 16 . In a precursor to this qualitative study, investigators conducted a quantitative study aimed at describing EBP attributes among Association of California Nurse Leaders (ACNL) members, representing multiple organizations throughout California (CA) 17 . This study found that CA NLs scored higher on all aspects of EBP beliefs, knowledge, and competencies scales compared with a national sample yet were challenged in advancing cultures that embrace EBP 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnet designation moved organizations toward nursing excellence by supporting organizational EBP implementation as a scholarly activity, as well as a core requirement for designation 16 . In a precursor to this qualitative study, investigators conducted a quantitative study aimed at describing EBP attributes among Association of California Nurse Leaders (ACNL) members, representing multiple organizations throughout California (CA) 17 . This study found that CA NLs scored higher on all aspects of EBP beliefs, knowledge, and competencies scales compared with a national sample yet were challenged in advancing cultures that embrace EBP 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In a precursor to this qualitative study, investigators conducted a quantitative study aimed at describing EBP attributes among Association of California Nurse Leaders (ACNL) members, representing multiple organizations throughout California (CA) 17 . This study found that CA NLs scored higher on all aspects of EBP beliefs, knowledge, and competencies scales compared with a national sample yet were challenged in advancing cultures that embrace EBP 17 . To achieve higher quality and safe cost-effective care, study findings indicated that NLs need to invest in providing resources to support an EBP culture 14,17 …”
Section: Introductionmentioning
confidence: 99%
“…PNOs provide nurses with service opportunities on committees, workgroups, and boards. Recognizing that leadership growth is essential for nurses, many PNOs offer specific programs targeting leadership competency development, which augments experiences in traditional practice environments 1-3,5…”
mentioning
confidence: 99%
“…Recognizing that leadership growth is essential for nurses, many PNOs offer specific programs targeting leadership competency development, which augments experiences in traditional practice environments. [1][2][3]5 • Policy and advocacy. PNOs help nurses strengthen their policy acumen by organizing visits with policy makers at the local, state, and national levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation